ENKULTURASI DISIPLIN DALAM MENINGKATKAN NILAI PENDIDIKAN KARAKTER RELIGIUS DI MI PSM GEDORO - Asroriah, Fatimatul (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2021)
Discipline enculturation can be defined as a process of introducing norms or values that apply based on an awareness of the importance of values and the importance of regulations and prohibitions of guidance towards improvement through the influence of implementation. This study aims to find out how to cultivate discipline and its impact on the regius values in MI PSM GEDRO. In this study, the researcher used a qualitative-analytic approach with the focus of the study being the enculturation of disciplines in inculcating the religious character values of MI PSM Gedoro students. The data analysis technique uses four stages, namely: data collection, data condensation, data presentation, and verification/conclusion. Discipline culture (discipline enculturation) and religious character values are two characters and attitudes that influence and perfect each other in the process of their formation. In other words, religious character will not be formed perfectly without discipline, and vice versa. Thus, the enculturation of discipline greatly affects the increase in the value of the religious character of the students of MI PSM Gedoro, which with the cultivation of discipline in the school environment, some religious character values can be embedded in students, especially students of MI PSM Gedoro